ORGANIC AGRICULTURE PRODUCTION IN GREEN ECONOMY DEVELOPMENT IN REPUBLIC OF NORTH MACEDONIA - Hadzi Naumova-Mihajlovska K. (Institute of economics-Skopje, 2022)
The main goal of the paper is to analyses the role and contribution of organic agricultural production on the development of concept of green economy in the Republic of North Macedonia. Both concepts, the organic agriculture and green economy are founded on the interaction of humans with the biophysical environment and offer numerous opportunities for improving the standard of living, developing underdeveloped countries and achieving sustainable development. Organic agriculture represents system of production which is based on the natural cycles and biodiversity, has well-defined principles and standards, as well as a certification system, and direct and indirect effects on people and the environment, and thus has direct linkages to the principles of a green economy. Organic agricultural sector in Republic of North Macedonia has significant place in the country, the interest for dealing with this production is continuously increased and the State support is continuously present. However, it is necessary to identify the main possibilities in organic agriculture, specifically organics agriculture production that contribute most to the economic growth and sustainable development in terms of green development opportunities in the country.
Keywords: organic agriculture, organic production, green economy, Republic of North Macedonia